Effects of required rates of responding upon choice - Fantino, Edmund (1968)
Pigeons' responses in the presence of two concurrently available (initial-link) stimuli produced one of two different (terminal-link) stimuli according to identical but independent variable-interval schedules. Responses in the presence of each terminal-link stimulus produced equal frequencies of food reinforcement, but in the presence of one of the stimuli, food depended upon the emission of a response rate either higher or lower than a specified value (differential reinforcement of rates). The measure of preference, the dependent variable, was the distribution of responses in the presence of the concurrently available stimuli of the initial links. Each pigeon, the responding of which was appropriately controlled by the response-rate requirements in the two terminal-link stimuli, consistently preferred the stimulus not associated with a response-rate requirement.